Kinship Analysis Malay And Gayo Language : A Comperativ Historical Linguistic Study - Prima Sholihatun; Dwi Widayati (CV. AFDIFAL MAJU BERKAH, 2022)
This study aims to reveal a relationship between Gayo and Malay which can be seen from the similarity of vocabulary. The method used is descriptive qualitative and quantitative. The data is in the form of vocabulary from Malay and Gayo language which has 6% similarity. This data can be proven not to have a close relationship because the core vocabulary is less than 36% or part of the sub grouping. This research also uses qualitative and quantitative methods. Mahsun (2005) states that qualitative is a way of grouping derived languages into a group that is closer to their relationship, and then using lexicostatistical techniques to analyze the data that has been collected..